2015
DOI: 10.17221/288/2014-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Fruit set and quality of self-fertile sweet cherries as affected by chemical flower thinning

Abstract: Milić B., Keserović Z., Dorić M., Ognjanov V., Magazin N. (2015): Fruit set and quality of self-fertile sweet cherries as affected by chemical flower thinning. Hort. Sci., 42: 119-124.Self-fertile cherry cultivars can produce an excessive crop of small fruits with low sugar content. In order to prevent overcropping and provide high quality fruits, chemical thinning of flowers is required. Ammonium thiosulfate (ATS), surfactants and plant oils are used to thin flowers, mostly in apple and peach. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…The literature mentions a similar effect after applying 2% ATS to 'Bing'/'Gisela 5' cherries [41]. In other studies, ATS was effective with 20.4 or 30.6 g/l, while the dose of 10.2 g/l had no effect on the fruit set [59]. ATS effectiveness on crop was also confirmed by studies conducted in Switzerland on four self-sterile varieties of cherries [43].…”
Section: Effect Of Thinning Treatments On Yield and Productivitymentioning
confidence: 70%
See 1 more Smart Citation
“…The literature mentions a similar effect after applying 2% ATS to 'Bing'/'Gisela 5' cherries [41]. In other studies, ATS was effective with 20.4 or 30.6 g/l, while the dose of 10.2 g/l had no effect on the fruit set [59]. ATS effectiveness on crop was also confirmed by studies conducted in Switzerland on four self-sterile varieties of cherries [43].…”
Section: Effect Of Thinning Treatments On Yield and Productivitymentioning
confidence: 70%
“…, [61]. According to earlier studies on cherries, TSS in the fruit could be more influenced by the cultivar and the course of weather conditions than by thinning operations [59] and the year [43]. Thinning had an effect on TSS in the full crop years (2009 and 2012), whereas it affected acidity only in 2012.…”
Section: Effect Of Thinning Treatments On Yield and Productivitymentioning
confidence: 99%
“…It has been reported that the use of 2% ATS does not cause visible signs of leaf damage [75]. However, at higher concentrations (3%), ATS was found to cause visible phytotoxicity on leaves, and at lower concentrations (1 and 2%), it did not reduce fruit set [6]. To reduce fruit set without damaging the leaves ATS can be applied twice at a concentration of 2%, as shown in the study on 'Bing' cherries grown on 'Gisela 5' rootstock, which yielded less fruit of better quality after the treatment [75].…”
Section: Chemical Thinningmentioning
confidence: 93%
“…However, cherry trees on dwarf rootstocks often bear an excessive number of small fruit with low sugar content [5]. Therefore, flower thinning is necessary to prevent over-yielding and to provide high-quality fruit [6,7] in terms of the basic fruit quality parameters, such as size, colour, total soluble solids, and firmness [2].…”
Section: Introductionmentioning
confidence: 99%
“…Fruit trees grown on dwarf and semi-dwarf rootstocks set more flower buds [5]. However, cherry trees on dwarf rootstocks often bear an excessive number of small fruit with low sugar content [6]. Therefore, flower thinning is necessary to prevent over-yielding and provide high-quality fruit [6,7] in terms of the basic fruit quality parameters, such as size, colour, total soluble solids, and firmness [2].…”
Section: Introductionmentioning
confidence: 99%